(3eNJUQ eaQOGJ GdRgQGhi aj efGaY GdeaQOGJ hNhGUgGs - (3eLghds ((3YHO GdeMSf Hf Ydi GdMSfi GdbGOQi s)
(3ChdgG (B:s
(3hHYO (B: (3bGd CHh GdbGSe Nda Hf YHGS GdRgQGhi (B: (3GYde Cf GdGSJYeGd dLejY GdCOhjI hGdhbha Ydi GNJdGa dZGJ CSeGFgG hUhQ CTNGUgG s
(3BNQgG (B:s
(3jQHhY (B: (3dMeg jZPh ZPGA cKjQkG hjdjf GdHWf , hdjcf gPG BNQ eG CQOfG LgI ef GdeaQOGJ GdRgQGhjI Ydi MSH GdWGbI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B44 - (3U(B87s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdWHs